The flipped classroom: Improving critical thinking for critical reading of EFL learners in higher education - Ryani Yulian (Universitas Syiah Kuala, 2021)
The immersion of the flipped classroom teaching model in blended and online language learning is indispensable. The purpose of this study was to propose improvement in critical thinking in reading through the flipped classroom teaching model of EFL (English as a Foreign Language) learners in higher education. A quasi-experimental design was used to improve reading skills based on the framework of critical thinking for critical reading with a paired t-test of pre-test and post-test. The participants were 37 second-semester students in the English for Academic Purposes class. The results show that the flipped classroom teaching model enhanced students’ critical thinking for critical reading in the aspects of accuracy, clarity, precision, depth, relevance, and logic from the mean score of the pre-tests (12.4865) to the post-tests (18.3243). Students had a positive perception of the implementation of this model in terms of self-directed learning. This study implies that critical thinking for critical reading skills needs supportive teaching and learning environment that can allow students to have self-study prior to the class so that online learning can be effective to synergize the application of flipped classrooms with critical thinking skills in reading.